Copper(II) Clusters of Two Pairs of 2, 3‐Dihydroxybutanedioyl Dihydrazones: Synthesis, Structure, and Magnetic Properties. Issue 33 (8th October 2014) - Chen, Zilu; Zhou, Suping; Shen, Yanling; Zou, Huahong; Liu, Dongcheng; Liang, Fupei
Abstract: Condensation reactions of (2 R, 3 R )‐ and (2 S, 3 S )‐2, 3‐dihydroxybutanedihydrazide with salicylaldehyde and 3‐methoxysalicylaldehyde gave two enantiomeric pairs, (2 R, 3 R )/(2 S, 3 S )‐2, 3‐dihydroxybutanedioylbis(salicylaldehydehydrazone) [(2 R, 3 R )‐BSH and (2 S, 3 S )‐BSH] and (2 R, 3 R )/(2 S, 3 S )‐2, 3‐dihydroxybutanedioyl bis(3‐methoxysalicylaldehydehydrazone) [(2 R, 3 R )‐MBSH and (2 S, 3 S )‐MBSH]. Their reactions with Cu II salts provided two chiral hexanuclear clusters [Cu6 L2 (C5 H5 N)10 ]2 [C5 H6 N]3 (ClO4 )7 · (CH3 OH)· (C5 H5 N) [L = (2 R, 3 R )‐BSH; (2 S, 3 S )‐BSH] and four chiral tridecanuclear clusters [Cu13 L3 (OH)2 (CH3 COO)6 (C5 H5 N)6 (DMF)3 ]· 6DMF· 3H2 O [L = (2 R, 3 R )‐BSH; (2 S, 3 S )‐BSH] and [Cu13 X3 (OH)2 (CH3 COO)6 (C5 H5 N)2 (DMF)8 ]· 6H2 O [X = (2 R, 3 R )‐MBSH, (2 S, 3 S )‐MBSH]. Their structures were determined by single‐crystal X‐ray diffraction analysis. All six compounds are enantiomers of each other. The two hexanuclear clusters exhibit two orthogonal linear trinuclear units. The two pairs of tridecanuclear clusters display esthetic structures with different symmetries; they feature rare heptanuclear vertex‐sharing dicubane cores and their six unshared Cu II vertexes are linked to another six Cu II ions. These represent the first examples of chiral clusters bearing dicubane cores. Magnetic studies revealed the presence of overall antiferromagnetic interactions in these compounds. Abstract : Six chiral clusters of two pairs of 2, 3‐dihydroxybutanedioyl dihydrazones, four of which represent the first examples of chiral clusters bearing dicubane cores, are presented. All six compounds are enantiomers of each other. Magnetic studies reveal the presence of overall antiferromagnetic interactions in these compounds.